Effects of process parameters on mechanical expression of soya bean oil - Garba, Anebi Joseph; Umogbai, Victor Imolemhe; Obetta, Samuel Enyi; Awulu, John Okanagba (Journal of Postharvest Technology, 2020)
This paper concentrated on the problems of apple fruit growers in Jammu and Kashmir state during 2018-19. With the help of the random  sampling method, 224 apple fruit growers were selected and data were collected by personal interview method by using a pre-tested interview  schedule. Lack of storage facilities, Lack of Packaging material, Malpractices by commission agents, poor road and transport, shortage of  labour, lack of facility of processing centres etc were the major problems expressed by the apple fruit grower. Different statistical test has been  used in the study like Mean; Mean per cent Score, Correlation, Rank and Z test etc. The results found that Small fruit growers faced more  problems as compared to large growers. The policymakers and developmental agencies should have to overcome these problems as the  apple is the major cash crop of these districts in particular and the region as a whole.
Keywords: Process; soya bean; oil extraction; mechanical expression